PENGARUH KONFORMITAS DAN TIPE GAYA HIDUP TERHADAP LOYALITAS MEREK PADA KONSUMEN STARBUCKS COFFEE DI KOTA BANDUNG - Lestari, Erina Ayu (2016)
Penelitianinibertujuanuntukmemperoleh data empiriktentangpengaruhkonformitasdantipegayahidupterhadaployalitasmerekpadakonsumen Starbucks di Kota Bandung. Respondenpenelitianiniadalahkonsumen Starbucks di Kota Bandung yang berstatusmahasiswaberjumlah 171 orangdenganmenggunakanteknikpuropose sampling.Adapundalampenelitianinimenggunakanpendekatankuantitaifdenganmetodeteknikanalisisregresi.Penelitianinimenghasilkantemuanbahwa. 1) Jeniskonformitasacceptance berpengaruhsebesar 42.6% terhadaployalitasmerek Starbucks Coffee di Kota Bandung. 2) Tipegayahdupfashion berpengaruhsebesar 16.5% terhadaployalitasmerek Starbucks Coffee di Kota Bandung3) MayoritaskonsumenStarbucks Bandung yang berstatusmahasiswacukup loyal terhadapmerek Starbucks. 4)Mayoritaskonsumen Starbucks Bandung yang berstatusmahasiswacenderungmelakukanjeniskonformitasacceptance dandidominasiolehtipegayahidupfashion. ;--- The purpose of this research is to get empirical data about conformity influence and lifestyle type to brand loyalty on Starbucks consumer in Bandung city. Respondents for this research are consumer of Starbucks in the city of Bandung which student amount to 171 people by using purpose sampling technique. As in this study using a quantitative approach with methods of analysis regression technique.This research finding that 1) A kind of conformity acceptance effetcs 42.6% on brand loyalty Starbucks Coffee in Bandung. 2) Fashion lifestyle type effects 16.5% on brand loyalty Starbucks Coffee in Bandung. 3) The majority of consumers Starbucks Coffee is a student are quite loyal to the Starbucks brand. 4) The majority of consumers Starbucks coffee in Bandung is a studentthat tends to do the kind of acceptance conformity and has the type of lifestyle fashion.